2021
DOI: 10.3390/antiox10121941
|View full text |Cite
|
Sign up to set email alerts
|

Mentha arvensis Essential Oil Exerts Anti-Inflammatory in LPS-Stimulated Inflammatory Responses via Inhibition of ERK/NF-κB Signaling Pathway and Anti-Atopic Dermatitis-like Effects in 2,4-Dinitrochlorobezene-Induced BALB/c Mice

Abstract: The mechanism of atopic dermatitis (AD) is modulated by the release of cytokines and chemokines through the mitogen-activated protein kinase (MAPK)/nuclear factor-kappa B (NF-κB) signaling pathway. Topical steroids are used to treat AD, but some people need safer anti-inflammatory drugs to avoid side effects. Mentha arvensis has been used as a herbal plant with medicinal properties, but its anti-inflammatory effects have not been elucidated in an AD model. In this study, we investigated the anti-inflammatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 54 publications
3
30
0
Order By: Relevance
“…In previous studies, H 2 O 2 was shown to activate the MAPK cascade in SH-SY5Y cells [ 46 ] and FMA extract and its active chemical substances downregulated MAPK protein expression levels [ 19 ]. In the present study, pretreatment with FMA significantly reduced increased phosphorylated ERK, JNK, and p38 MAPK levels in the hippocampus and SH-SY5Y cells, which supports the results of previous studies [ 19 , 47 ]. Taken together, FMA pretreatment could reduce TI and H 2 O 2 -induced neurotoxic effects in gerbil hippocampus and SH-SY5Y cells respectively by inhibiting the MAPK signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, H 2 O 2 was shown to activate the MAPK cascade in SH-SY5Y cells [ 46 ] and FMA extract and its active chemical substances downregulated MAPK protein expression levels [ 19 ]. In the present study, pretreatment with FMA significantly reduced increased phosphorylated ERK, JNK, and p38 MAPK levels in the hippocampus and SH-SY5Y cells, which supports the results of previous studies [ 19 , 47 ]. Taken together, FMA pretreatment could reduce TI and H 2 O 2 -induced neurotoxic effects in gerbil hippocampus and SH-SY5Y cells respectively by inhibiting the MAPK signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…S-Y Kim et al demonstrated the effects of Mentha arvensis essential oil on lipopolysacch aride-induced inflammatory stimulation in RAW 264.7 macrophages and HaCaT keratinocytes [14]. This research team confirmed the possibility of applying these findings to an AD model.…”
mentioning
confidence: 56%
“…Early studies indicated that HDM (45), DNCB (46), ovalbumin (47), and calcipotriol (48) cause exacerbation of AD. DNCB is often used to induce AD in mouse models of AD, as the results are highly reproducible and repeatable (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%